2019
DOI: 10.1155/2019/9897831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Highway Landscapes on Drivers’ Eye Movement Behavior and Emergency Reaction Time: A Driving Simulator Study

Abstract: This study aims at investigating the effects of highway landscapes and alignments on drivers’ eye movement behavior and emergency reaction time, based on a driving simulator experiment. In this study, four simulation scenarios are evaluated including open space, semiopen space, semiclosed space, and enclosed space landscapes on highways in Yunnan Province, China. Twenty-four experienced drivers participated in a 6-kilometer driving experiment in each landscape scenario. Each subject was required to drive at 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…People driving regularly to office and those of the large goods vehicles require a pleasant, long drive away from the urban traffic and crowd. While driving can be considered a stressful activity, the lack of a scenic landscape with no prominent landmarks or changes in the scenery, only aggravates the driver on an expressway (Guo et al, 2019). As in Figure 7, broken kerbs serving as a median separator between the incoming and outgoing road lanes with no prominent signage at access points only confuses the new user entering this expressway.…”
Section: Aesthetic Impactmentioning
confidence: 99%
“…People driving regularly to office and those of the large goods vehicles require a pleasant, long drive away from the urban traffic and crowd. While driving can be considered a stressful activity, the lack of a scenic landscape with no prominent landmarks or changes in the scenery, only aggravates the driver on an expressway (Guo et al, 2019). As in Figure 7, broken kerbs serving as a median separator between the incoming and outgoing road lanes with no prominent signage at access points only confuses the new user entering this expressway.…”
Section: Aesthetic Impactmentioning
confidence: 99%
“…The spatial pattern is a three-dimensional concept :stereoscopic dimension is perpendicular to the road surface; vertical dimension is parallel to the direction of the road (Figure 1); horizontal dimension is perpendicular to the direction of the road (Figure 1). In the stereoscopic dimension, Zheng et al found that the emergency time and average speed decreased with the increase of enclosure [17,18]. Moreover, a survey of traffic calming activities in Minnesota shows that once vegetation is removed, the sense…”
Section: Spatial Pattern Design Of Landscapementioning
confidence: 99%
“…In the stereoscopic dimension, Zheng et al . found that the emergency time and average speed decreased with the increase of enclosure [17,18]. Moreover, a survey of traffic calming activities in Minnesota shows that once vegetation is removed, the sense of closure will disappear, and drivers will respond by increasing driving speed [19]; In the vertical dimension (Figure 1), Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is how the eye tracking technique was born. Eye tracking can obtain the focus of sight in real time and be applied to analyze the user's eye movement in reading [3] or in a critical state [4], so as to infer the user's content of interest in reality [5,6]. Furthermore, it can also be used for the prediction and treatment of patients with brain neurological diseases [7,8].…”
Section: Introductionmentioning
confidence: 99%